P–794 Prevalence of positivity for SARS-CoV–2 RNA in follicular fluid in infertile patients. (6th August 2021) - Porcu, E; Cipriani, L; Dirodi, M; Calza, N; Ciotti, P M; Tranquillo, M L; Notarangelo, L; Zuffa, S; Labriola, F S; Vocale, C; Damiano, G
Abstract: Study question: Is Sars-Cov–2 present in the follicular fluid of infertile patients? Summary answer: In the experience of the Infertility and IVF Unit, University Of Bologna, Italy, RNA of SARS-Cov–2 was not detected in the follicular fluid. What is known already: Data on the risk of virus presence in reproductive cells and transmissibility in IVF procedures are very limited. In literature only one study reports the detection of SARS-Cov–2 viral RNA in oocytes of PCR positive women. Research of RNA in follicular fluid could be a marker able to indicate whether to continue IVF treatments in the case of swab-positive patients. Study design, size, duration: Prospective study performed at Infertility and IVF Unit, Sant'Orsola University Hospital, University of Bologna, Italy, from March 2020 to January 2021. 451 IVF cycles were performed on 902 patients. In addition 59 cycles of oocyte cryopreservation were also performed to fertility preservation in oncological patients. In all positive swab patients was analyzed the follicular fluid for RNA virus detection. Participants/materials, setting, methods: 961 patients underwent telephone triage before going to the IVF Center to identify subjects with suspected or confirmed infection. Body temperature was measured on all patients before entering the IVF Center. All patients were subjected to real-time analysis (RT PCR) of pharyngeal swab samples 48 hours before transvaginal ultrasound-guided oocyte retrieval. In case of positive swab, PCR was performed on follicular fluid. Main results and the role of chance: In our population of infertile patients the incidence of SARS COV–2 infection positivity was 0.4% (4/961). No IVF treatments were suspended. The oocytes of the 4 women with positive swab were cryopreserved using closed devices stored in a special dedicated cryogenic container. No viral RNA was detected in the follicular fluid. Limitations, reasons for caution: there are no limitations to the study. Wider implications of the findings: The absence of SARS-COV–2 RNA in the follicular fluid is a reassuring result in the storage and future use of oocytes. Trial registration number: Not applicable